Neural evidence of task efficacy affecting cognitive control in test-anxious individuals. - Ou, Yuhong; Zhou, Renlai (Cognitive, Affective & Behavioral Neuroscience, 2025)
Recent studies have found cognitive control deficits in high test anxiety (HTA) individuals, yet the underlying mechanisms remain incompletely understood. Guided by the Expected Value of Control (EVC) model, this study used a mixed factorial design to examine how task efficacy influences cognitive control in individuals with HTA. We utilized event-related potentials (ERPs) in a cued Flanker task, manipulating the evaluative threat context and task difficulty. Behavioral results showed that in threat contexts, HTA individuals exhibited longer reaction times in the Flanker task and lower accuracy in high-conflict conditions compared to low test anxiety (LTA) individuals. The results of ERP showed that during cue processing, HTA individuals exhibited exaggerated contingent negative variation (CNV) amplitudes across all difficulty cues in nonthreat contexts, suggesting excessive preparatory activity and resource allocation. However, in threat contexts, CNV amplitudes were significantly reduced, reflecting inadequate cognitive resource mobilization. During cognitive control processing, HTA individuals exhibited more negative N2 amplitudes in high-conflict conditions in nonthreat contexts, suggesting enhanced cognitive control. In contrast, in threat contexts, their N2 amplitudes were significantly more positive than those of LTA individuals, indicating impaired cognitive control. The study found that HTA individuals overinvested cognitive resources in nonthreat contexts but reduced investment in threat contexts, possibly due to lower perceptions of efficacy, which may have impaired cognitive control. This research extended the application of the EVC model, provided new theoretical insights into the mechanisms of cognitive control deficits in test anxiety, and informed targeted interventions.